2020
DOI: 10.3390/cancers12010219
|View full text |Cite
|
Sign up to set email alerts
|

Cell Electropermeabilisation Enhancement by Non-Thermal-Plasma-Treated PBS

Abstract: The effectiveness of electrochemotherapy (ECT) in local eradication of tumours in human and veterinary medicine has been proven. ECT consists of increasing the uptake of cytotoxic drugs by means of pulsed electric fields (PEFs) that transiently permeabilise the cell membrane. Still, this tumour treatment includes some drawbacks that are linked to the characteristics of the intense electric pulses (EPs) used. Meanwhile, the emerging field of cancer therapies that are based on the application of non-thermal plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…We found that plasma treatment followed by PEF exposure led to a modest increase in the irreversible electroporation of lymphoma cells. This corroborates previous findings using plasma-treated PBS [38]. In addition, our results showed a markedly increased cytotoxicity in the combination of the mono-treatments.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that plasma treatment followed by PEF exposure led to a modest increase in the irreversible electroporation of lymphoma cells. This corroborates previous findings using plasma-treated PBS [38]. In addition, our results showed a markedly increased cytotoxicity in the combination of the mono-treatments.…”
Section: Discussionsupporting
confidence: 93%
“…Our second hypothesis was that the combination of plasma and PEF augments ROS production cell death signaling [29,34,35]. While three previous studies investigated the combination of plasma-treated liquids and PEF on cancer cells [36][37][38], our study aimed at elucidating the underlying mechanism of direct plasma treatment and pulsed electric fields (PEFs).…”
Section: Discussionmentioning
confidence: 99%
“…Studies also show that the combination of pulsed electric fields and ATNTP (or plasma‐treated liquid) can achieve a significant synergistic effect, whether on bacterial inactivation or on cell membrane electropermeabilization. [ 18,19 ]…”
Section: Introductionmentioning
confidence: 99%
“…This Special Issue on “Plasma in Cancer Treatment” brings together 16 original research papers [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and two insightful reviews [ 24 , 25 ]. The papers published in the Special Issue provide valuable information regarding the efficacy of CAP against osteosarcoma, glioblastoma, cholangiocarcinoma, melanoma, pancreatic, ovarian, breast, cervical and colorectal cancer.…”
mentioning
confidence: 99%
“…CAP has been used in combination with chemotherapeutics and radiation therapy to boost their cytotoxic activity [ 9 , 10 ] and to restore sensitivity to chemotherapeutics [ 11 ]. In combination with low pulse electric fields, CAP improves the permeabilization of cells [ 19 ], which could be beneficial for drug delivery. The addition of gold quantum dots to CAP treatment can further boost the efficacy of the treatment [ 13 ].…”
mentioning
confidence: 99%